2017
DOI: 10.1002/pssr.201700279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Tunable Photocurrent in La0.7Sr0.3MnO3/BaSnO3 Heterojunctions

Abstract: Artificially constructed oxide heterointerfaces have attracted much attention. Herein, the novel all-perovskite p-n heterojunction composed of a colossal magnetoresistive manganite La 0.7 Sr 0.3 MnO 3 (LSMO) and an n-type transparent semiconducting BaSnO 3 (BSO) is designed via optimizing the growth condition. This LSMO/BSO p-n junction exhibits good rectification with a forward-to-reverse ratio of 275 at 1 V, high photo detection capability with a photo-to-dark current of 581.9 at À0.5 V, high ultraviolet lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, compared to other physical methods such as pulsed laser deposition (PLD) and molecular beam deposition (MBE), sputtering techniques are more easily scaled for applications. Very recently, we demonstrated that the BSO films grown by radio frequency (RF) magnetron sputtering under a reduced oxygen atmosphere could modify the transport and magnetic photovoltaic properties of La 0.7 Sr 0.3 MnO 3 /BaSnO 3 junctions . These previous results indicated that defects if controlled properly could offer an alternative opportunity to engineer the physical properties of BSO films, because they may act as donors/acceptors, compensating centers, charge traps, or recombination centers.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, compared to other physical methods such as pulsed laser deposition (PLD) and molecular beam deposition (MBE), sputtering techniques are more easily scaled for applications. Very recently, we demonstrated that the BSO films grown by radio frequency (RF) magnetron sputtering under a reduced oxygen atmosphere could modify the transport and magnetic photovoltaic properties of La 0.7 Sr 0.3 MnO 3 /BaSnO 3 junctions . These previous results indicated that defects if controlled properly could offer an alternative opportunity to engineer the physical properties of BSO films, because they may act as donors/acceptors, compensating centers, charge traps, or recombination centers.…”
Section: Introductionmentioning
confidence: 92%
“…As the member of perovskite family, alkaline-earth stannates (RSnO 3 ; R = Ba, Sr, and Ca) have been intensively investigated for various applications. Among RSnO 3 , BaSnO 3 (BSO) with an ideal cubic perovskite structure and large optical band gap (>3 eV) is particularly promising. , La-doped BSO single crystals possess extremely high room-temperature mobility (∼320 cm 2 V –1 s –1 ) and excellent thermal stability, reflecting great prospects as a candidate transparent conducting oxide to replace the industry standard Sn-doped In 2 O 3 (ITO). In particular, the power conversion efficiency and the stability of organic–inorganic perovskite solar cells were improved by replacing mesoporous TiO 2 with La-doped BSO .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] In recent years, perovskite oxide heterostructures have attracted a lot of attention due to its potential applications compared with traditional p–n junctions. [ 3–6 ] As perovskite oxides have exotic electronic states, [ 7–9 ] the heterostructures which is composed of perovskite oxides, show plenty of interesting physical properties, such as rectifying characteristics, [ 10,11 ] photovoltaic effect, [ 12–14 ] positive colossal magnetoresistance, [ 15,16 ] resistive switching effect, [ 17 ] and so on. Numerous perovskite oxide heterostructures were developed for compound functional application, such as all‐oxide diode, memristor, solar cell, photodetector, and so on.…”
Section: Figurementioning
confidence: 99%